INTERNALISASI NILAI PENDIDIKAN UKHUWAH ISLAMIYAH, MENUJU PERDAMAIAN (SHULHU) DALAM MASYARAKAT MULTIKULTURAL PERSPEKTIF HADIS - Ali Ridho (AT-TAJDID, 2017)
This Paper used library research approach  that aimed to answer the phenomena that happened this era that paid attentions to the peoples that break the brotherhood. In the politic issue at Jakarta, created dualism between one community to others, diversity become headline issue and instrument/tool of power. While Jakarta as the capital of Indonesia being   prototype and indicator of the human adolescent index of state. Multiculturalism interpretation being in hesitate when talked about politic and poverty. Demonstrations and peace refused non muslim being headline and viral. This paper concluded that to make a peace (shulhu), brotherhood (ukhuwah) should constructed as well as the prophetic message that ukhrawi minded. Because the brotherhood now a day already had been broke by the materialism and pragmatism . In Islam the concept of Brotherhood education is how to strength and organizing a hearth (tandzim al-qolb) and love the people by the name of Allah, through three parts of brotherhood (ukhuwah); Ukhuwah Islamiyah, Ukhuwah Wathaniyah, dan Ukhuwah Basyariyah.